Modeling the Ukraine Black Sea Economic Region GRP Dependence on Socio-Economic Indicators - Bulgakova, O. (Індуктивне моделювання складних систем, 2013)
This paper presents the results of simulation socio-economic and ecological processes on example of the southern Ukraine under conditions of incomplete information. Construction and implementation of the information technology computer monitoring model of the complex processes state at various levels Представлено результати моделювання соціально-економічних явищ та екологічних процесів системного характеру на прикладі півдня України в умовах неповноти інформації. Сконструйована та реалізована типова інформаційна технологія комп’ютерного моніторингу стану складних процесів різного рівня. Представлены результаты моделирования социально-экономических явлений и экологических процессов системного характера на примере юга Украины в условиях неполноты информации. Сконструированная и реализована типовая информационная технология компьютерного мониторинга состояния сложных процессов разного уровня.